The name of the game is a kidnapping ebook - Higashino, Keigo (2017)
Battle-tested project leader at a PR firm and slippery bachelor, Sakuma sees himself as a player. His smug self-regard doesn't seem entirely unfounded, both in love and at work. When is idea for a mini-theme park is dismissed as too costly and vacuous at the last minute by a major client he seems to have met his match. Katsuragi, an heir and executive at the global car maker, Nissei Auto, is back from a marketing stint in the US with an authentic conviction that everything is a game. Once the man's daughter by a former mistress teams up with Sakuma so she can come into her inheritance in an expeditious manner—Juri is indeed her father's flesh and blood—the game is good to go! And the name of this game is a kidnapping!